2011
DOI: 10.21829/azm.2011.272756
|View full text |Cite
|
Sign up to set email alerts
|

Ciclo de vida y parámetros poblacionales de Sympherobius barberi Banks (Neuroptera: Hemerobiidae) criado con Dactylopius opuntiae Cockerell (Hemiptera: Dactylopiidae)

Abstract: El nopal verdura, Opuntia ficus-indica, es una hortaliza de importancia económica, social y ambiental en México, y una de sus plagas más importantes es la cochinilla silvestre del nopal, Dactylopius opuntiae. De sus enemigos naturales nativos el hemeróbido depredador Sympherobius barberi es una posible alternativa para su control. El objetivo de esta investigación fue estudiar la biología de S. barberi alimentado con D. opuntiae. Para establecer las crías en laboratorio tanto de la presa D. opuntiaey el depred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
4
0
3
Order By: Relevance
“…The total development time from egg hatch to adult emergence was 26–28 days for S. barberi in the present study. Pacheco-Rueda et al (2011) reported similar development time for this predator on the diet of Dactylopius opuntiae . Lara and Perioto (2003) reported that several species of hemerobiids complete their life cycle in 23–40 days at 23°C, and Vargas (2007) stated 23 days life cycle for Chrysoperla carnea at 26°.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The total development time from egg hatch to adult emergence was 26–28 days for S. barberi in the present study. Pacheco-Rueda et al (2011) reported similar development time for this predator on the diet of Dactylopius opuntiae . Lara and Perioto (2003) reported that several species of hemerobiids complete their life cycle in 23–40 days at 23°C, and Vargas (2007) stated 23 days life cycle for Chrysoperla carnea at 26°.…”
Section: Discussionmentioning
confidence: 61%
“… Pacheco-Rueda et al (2011) observed an average adult longevity of 39 days for S. barberi on the diet of Dactylopius opuntiae and average of 1.89 eggs per day per female. In the present study, S. barberi adults evaluated in the two experiments lived between 13 and 19 days, on the diet of D. citri , and female produced an average of 25 eggs during a 3-week period, the latter not very different from the previous study.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…La cochinilla silvestre del nopal es la plaga más importante del nopal verdura en San Luis Potosí, al incrementarse la superficie cultivada, ampliarse la época de producción y por el mal manejo de agroquímicos (García et al, 2008;Luna, 2011;Pacheco et al, 2011). Cabe mencionar, que el control químico, especialmente es el uso de insecticidas organofosforados que es la herramienta más común (Palacios et al, 2004), no es eficiente y causa daños al ambiente y a la salud de los trabajadores.…”
unclassified
“…En la zona de estudio la incidencia de cochinilla silvestre se presenta de abril a septiembre (García et al, 2008), el tiempo entre generaciones varia de 35-45 días (Pacheco et al, 2011) y los factores que dificultan el control de esta plaga son su cubierta cerosa, su resistencia a factores climáticos adversos, altas tasas de reproducción y ciclo de vida corto (Pacheco et al, 2011). El daño en nopal lo ocasionan las hembras, tanto ninfas como adultas ya que, al extraer savia, provocan amarillamiento, el debilitamiento y muerte de la planta (Vanegas et al, 2010).…”
unclassified